PENGARUH INSIDER OWNERSHIP, INSTITUTIONAL OWNERSHIP, DISPERSION OF OWNERSHIP, COLLATERALIZABLE ASSETS, DAN BOARD INDEPENDENCE TERHADAP KEBIJAKAN DIVIDEN PADA SEKTOR FINANCE PERIODE 2011-2015 - VIOLETTA MANGASIH, GREVIA (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this study is to examine the factors influencing the dividend policy, namely, insider ownership, institutional of ownership, dispersion of ownership, collateralizable assets, and board independence. The factors influencing this dividend policy were checked by using method of Logit Regression.Having studied using logit regression, the results obtained that there are three factors that influence the dividend policy, namely, insider ownership, institutional of ownership, and collateralizable assets. Insider ownership negatively affected the dividend policy since the increasing number of insider ownership increased the control of the company so that the shareholders felt safe to reinvest. Institutional of ownership negatively affected the dividend policy since the institutions had a majority stake in the company so that little fraud occurring which made them reinvest. Collateralizable assets positively affected the dividend policy since greater collateralizable assets increased the distribution of dividends to shareholders. While there are two factors that did not affect the dividend policy, namely, the dispersion of ownership and board independence. The dispersion of ownership did not affect the dividend policy because the results of the data obtained show that the shareholding in the company was only < 5%. Thus, the influence of decision-making was small. Furthermore, board independence also had no effect on dividend policy because the independent commissioners were only part of the board of commissioners. Keywords: dividend policy, insider ownership, institutional ownership, dispersion of ownership, collateralizable assets, board independence.